Translation of scientific evidence into cardiovascular guidelines. Issue 4 (14th December 2021) - Koller, Akos; Takács, Johanna
ABSTRACT: Introduction and aims: Research evidence is the basis of guidelines used by healthcare professionals to make difficult decisions every day. We hypothesized that due to the available evidence the four selected cardiovascular guidelines have different degrees of certainty for making efficient decisions. Methods: We conducted an analytic study on the guidelines on arterial hypertension (AH), myocardial revascularization, syncope and cardiovascular diseases during pregnancy to assess the levels of evidence (LEVEL) and the classes of the recommendations (CLASS). Results: A total of 636 LEVEL and CLASS data were analyzed. To define certainty, LEVEL areas under CLASS were calculated. The frequency of LEVEL by CLASS showed that AH had the highest rate of evidence A in each CLASS. Myocardial revascularization showed a frequency pattern similar to that of AH. In syncope and pregnancy, the percentage of evidence B and/or C was the highest in each class; the percentages of certainty were 24.3% – pregnancy and 75.7% – AH. Deviations from an optimal decision revealed that the observed percentages of certainty were significantly lower on higher LEVEL than the expected percentages. Conclusion: Analyzing recommended procedures for diagnosis and treatments revealed a great disparity of certainty among the guidelines, and that the guideline of AH is superior to other guidelines, probably due to the substantial scientific evidence available in this field. Revealing the ratio of certainty/uncertainty in guidelines can identify issues to be clarified and investigated in future studies.